Digitalization Of Education In Madrasah - Sulaiman, Mohammad (Journal of Social Science and Economics, 2022)
In this era, the global community has assessed madrasa education as a human investment to prepare for a more successful future in this world and the hereafter. The rapid development of technology is able to bring changes to the world of Islamic education and does not diminish the hopes of many people that madrasas can co-exist with information technology in creating quality education. On the other hand, technological developments that can be consumed instantly and easily have given rise to alternative madrasa education in the global community with the concept of alternative education. When Islamic education in madrasas cannot be separated from the flow of globalization, preparation finds opportunities and challenges. Therefore, Islamic education in madrasas is required to play a role in solving moral, ethical and modern scientific problems. There is a need to reform education in madrasas to be able to face increasingly strong global challenges. In this case, the role of local stakeholders in its growth, digital era madrasas need to change the paradigm of Islamic education. The readiness of madrasas starting from teachers, facilities, and human resources must be prepared from now on so that they can create an educational atmosphere and environment that can be compatible with digital technology. In the future, the hope is that madrasa graduates can compete with all elements in the economic, social, cultural and industrial fields and other fields in terms of world affairs, where graduates are actually able to realize cultural values ??and local wisdom about values ??and norms, all of which are inherent in madrasas